2018
DOI: 10.4322/acr.2018.011
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic castration-resistant prostate cancer and the challenge of a patient with chronic kidney disease in hemodialysis

Abstract: At a time when the population shows increasing longevity, entities such as cancer and chronic kidney disease (CKD) are more frequently connected. In the United States, approximately 6% of the patients on hemodialysis have cancer. The challenge to manage oncologic patients with CKD in a hemodialytic program represents a great shortage of available information on the choice of the best drug, timing, dosage adjustments, dialysis method, and treatment safety. We present the case of a patient with prostate cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Therefore, the treatment was reported as safe in patients undergoing HD. Simoes et al preferred 160mg/day treatment and no side effects were reported (9). The treatment is ended 7 months later because of widespread progression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the treatment was reported as safe in patients undergoing HD. Simoes et al preferred 160mg/day treatment and no side effects were reported (9). The treatment is ended 7 months later because of widespread progression.…”
Section: Discussionmentioning
confidence: 99%
“…In similar case reports, no significant toxicities were observed. 10,11 Plasma levels were measured at 2 weeks, 1 month, and 2 months after the start of treatment. Although the first sample was taken while plasma concentrations were not yet at steady-state, the enzalutamide concentration was above the suggested target of 5.0 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Enzalutamide Plasma Concentrations During Hemodialysis treatment without pharmacokinetic assessment. 10,11 We present a case of enzalutamide treatment in a patient with end-stage renal disease undergoing hemodialysis, including plasma levels of enzalutamide, the active metabolite N-desmethyl enzalutamide, and the inactive metabolite enzalutamide carboxylic acid.…”
Section: Clinical Practice Pointsmentioning
confidence: 99%